The utility of the countermovement rebound jump for the assessment of neuromuscular status in National Collegiate Athletic Association Division I American football players - Talpey, S. W.; Haintz, L.; Drake, M.; Mundy, P. M.; Rayner, R.; James, L. P.; O'grady, M.; Gabbett, T. J.; Gardner, E. C. (The Journal of Strength and Conditioning Research, 2026)
The purpose of this study was to explore the sensitivity of the countermovement rebound jump (CMRJ) for assessing neuromuscular status after National Collegiate Athletic Association (NCAA) Division I American Football games. Twenty-nine male NCAA Division I American football players completed CMJ and CMRJ assessments 24 hours pregame, and at 24 and 72 hours postgame across 2 competitive matches. Jump testing was performed using dual force plates, and total PlayerLoad was recorded during games via Global Positioning System tracking. Linear mixed-effects models were used to examine the effects of time, match load, and game on CMRJ and CMJ metrics. Significant findings were followed by post-hoc pairwise comparisons and calculation of effect sizes. Significant time-dependent decrements were observed in CMRJ average power ( p = 0.001, d = 0.67), RSImod ( p = 0.03, d = 0.49), and jump height ( p = 0.046, d = 0.46) at 24 hours postmatch, with recovery evident in average ( p = 0.002, d = *0.63) and peak power ( p = 0.004, d = *0.60) by 72 hours. Countermovement jump height increased significantly by 72 hours ( p = 0.02, d = *0.49). Match load significantly mediated recovery trajectories for CMJ RSImod ( p = 0.004) and time to take-off ( p = 0.016), with higher loads associated with impaired recovery. The CMRJ appears to be more sensitive to acute fatigue. Whereas certain CMJ metrics were more sensitive to detecting how recovery trajectories were moderated by game load. The CMRJ offers practitioners a time-efficient and informative tool to assess the presence of acute fatigue after competition.